Events with an isolated lepton and missing transverse momentum and measurement of W production at HERA - Aaron, Francisc Dionisie; Herbst, Matthew; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (Journal of high energy physics, 2010)
A search for events containing an isolated electron or muon and missing transverse momentum produced in e±p collisions is performed with the H1 and ZEUS detectors at HERA. The data were taken in the period 1994-2007 and correspond to an integrated luminosity of 0.98 fb−1. The observed event yields are in good overall agreement with the Standard Model prediction, which is dominated by single W production. In the e+p data, at large hadronic transverse momentum PTX> 25GeV, a total of 23 events are observed compared to a prediction of 14.0 ± 1.9. The total single W boson production cross section is measured as 1.06 ± 0.16 (stat.) ± 0.07 (sys.) pb, in agreement with an Standard Model (SM) expectation of 1.26 ± 0.19 pb.